Produção teórica e teorização em educação a partir da ANPED - Veiga Júnior, Álvaro (2012)
This research aims to study processes of theoretical construction from their formative perspective, involving the pedagogic praxis of reading and writing, in the sphere where theoretical production and education meet. The focus of this study is composed by philosophical reflections from dialogs with research papers published by ANPED (National Association of Inquiry in Education), which is a forum that brings together investigators of areas of specialized knowledge in education. This work also invests in theorization as a formative verbal culture and grounds on education and language macro-scientificity, between philosophical, cultural perspectives and epistemological perspectives. We connect the interest to the curriculum and conceptualize it in an operational way so as to propose a scale of contributions and questions to the epistemology of education. We theorize when using a methodology developed in a movement creating tensions in the integration of several space-times which constitute lively places for the construction of the existence of student-teachers. While going along different texts published in ANPED‟s page, we find examples of the complex and multidimensional notion of processes of subjectivation. In contact with these texts, we systematize and (re)create categories, we enunciate the experience in dialogue with authors such as Paul Freire, - the reading of the world and the ethics of participant research; Jorge Larrosa, with essay, event and experience of reading and writing; and with Brazilian researchers who also teach: Carlos Rodrigues Brandão, Pedro Demo, Sílvio Sánchez Gamboa, Marcos Reigota, Tomaz Tadeu da Silva, Alfredo Veiga-Neto, Marisa Vorraber Costa and Carlos Walter Porto-Goncalves. Besides the contributions of classic texts in education, in the movement of study we bring near theorizations by Karl Marx, Friedrich Nietzsche and Michel Foucault, and make them converge in the worldview of this study. The work made efforts for creating textual links between an integrative multidimensional education and the increase in value of processes and means, increasing the repertoire and qualifying several knowledge areas aiming at theorizing. If teachers' education involves the paradigm of the product, which bureaucratizes and formalizes, there is also the search for the process and mediation. A discursive writing on the experience of language in the research pedagogical-political praxis implies inescapably a dose of not strictly academic essayism; and it cries out for a compensatory emphasis, of an ethical and esthetical character, in banking-education places and interests. Thus, the effort for presenting a praxical theorization as discursivity, and, with this, to contribute to an epistemic justice owed to education, to science as it is now practiced. A science that is not "neuter" or only committed invites us to make the pendulum be turned on behalf of the majoritarian minority. The model of inversion and compensation as an axiological scheme has been acting in the feeric indifferentiation of modernity while valuing contributions of wisdom and culture that integrate scientific knowledge and, so, must participate in its destiny. We try to create a dialogue with four articles of ANPED, which allowed to us to build the contextualization in the ideal horizon of argumentative or apprenticeship communities that build discursivities in the daily life of pedagogic praxis of research. Nevertheless, there are connections and links that are not visible in the products but are part of it, since any communitarian production fights for historical recognition and providing us opportunities to substitute gradually the culture of representation and heteronomy coming from the transmitting teaching of ready-made products. The via regia involves deeply apprenticeship, evaluation, and a non-consumerist citizenship. So, the curriculum may be a claim for the act of reading, writing, and living in the space-time of the world in movement, in order to maintain, to learn and to change.